2007
DOI: 10.1359/jbmr.070808
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Deficiency Causes Altered Expression of Molecules Critical for Calcium Reabsorption in the Kidneys of Female Mice

Abstract: Kidney stones increase after menopause, suggesting a role for estrogen deficiency. ArKO mice have hypercalciuria and lower levels of calcium transport proteins, whereas levels of the klotho protein are elevated. Thus, estrogen deficiency is sufficient to cause altered renal calcium handling. Introduction:The incidence of renal stones increases in women after menopause, implicating a possible role for estrogen deficiency. We used the aromatase deficient (ArKO) mouse, a model of estrogen deficiency, to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Roosters affected by epididymal lithiasis had increased levels of TRPV6 and CaBP-D28K but not PMCA and NCX1. It is known that modulation of expression of these proteins is under control of different hormones, such as vitamin D3, estrogens, and androgens (Cai et al 1993, Van Abel et al 2002, Kip & Strehler 2004, Hoenderop et al 2005, Oz et al 2007, Hsu et al 2010. On this sense, we showed recently that roosters with lithiasis presented altered levels of vitamin D3, E 2 , and testosterone that paralleled changes in their receptors (VDR, ESR2, and AR respectively) within the epididymal region (Oliveira et al 2011b).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Roosters affected by epididymal lithiasis had increased levels of TRPV6 and CaBP-D28K but not PMCA and NCX1. It is known that modulation of expression of these proteins is under control of different hormones, such as vitamin D3, estrogens, and androgens (Cai et al 1993, Van Abel et al 2002, Kip & Strehler 2004, Hoenderop et al 2005, Oz et al 2007, Hsu et al 2010. On this sense, we showed recently that roosters with lithiasis presented altered levels of vitamin D3, E 2 , and testosterone that paralleled changes in their receptors (VDR, ESR2, and AR respectively) within the epididymal region (Oliveira et al 2011b).…”
Section: Discussionmentioning
confidence: 72%
“…On this sense, we showed recently that roosters with lithiasis presented altered levels of vitamin D3, E 2 , and testosterone that paralleled changes in their receptors (VDR, ESR2, and AR respectively) within the epididymal region (Oliveira et al 2011b). The vitamin D3 and E 2 responsive systems are directly correlated with TRPV6 and CaBP-D28K expression levels (Hoenderop et al 2001, 2005, Oz et al 2007). However, the hormonal effect on the calcium extrusion step is less clear, although it has been shown that vitamin D3 stimulates PMCA expression in the basolateral membranes of reabsorptive cells in the intestine and kidney (Cai et al 1993, Kip & Strehler 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of vitamin D3 and E 2 are associated with increased calcium reabsorption, as they promote the expression of the transient receptor potential vanilloid channels (TRPV5), calbindin-D28k (CaBP-D28K), and plasma membrane calcium ATPase (PMCA), including in birds (Cai et al 1993, Hoenderop et al 2001, Van Abel et al 2002, Dick et al 2003, Kip & Strehler 2004, Oz et al 2007). These proteins participate on the entry of calcium within the cell, its diffusion throughout the cell cytoplasm to the basolateral membranes and calcium extrusion to the extracellular environment respectively (Hoenderop et al 2005).…”
Section: Steroids and Esr2 In Epididymal Lithiasismentioning
confidence: 99%